PERFORMANCE AND EMISSION ANALYSIS OF A DIESEL ENGINE USING ETHANOL-BLENDED FUEL: .. - Sher Muhammad Ghoto; Azhar Hussain Shah; Muhammad Kashif Abbasi; Aijaz Abbasi; Muhammad Shafique; Liaquat Ali; , Sajjad Bhangwar; Muhammad Ramzan Luhur (Spectrum of Engineering Sciences, 2025)
This study provides a comprehensive assessment of the performance and environmental implications of ethanol-blended fuels in a Compression Ignition (CI) engine, focusing on noise emissions, carbon monoxide (CO) emissions, brake. Results indicate substantial reductions in noise emissions, with ethanol-blended fuel E7D93 showcasing a decrease in noise emission level as compared with diesel fuel at different positions, such as the front position, top position, left position, and back position, compared to D100. These fuels also lead to a noteworthy decrease in carbon monoxide emissions, with reductions of 5.87% for E7D93 compared to D100. However, observe a slight increase in brake-specific fuel consumption with ethanol blends. In summary, this research highlights the potential of ethanol as an environmentally friendly additive for CI engines, offering reduced noise and emissions, along with improved engine efficiency, albeit with a minor trade-off in fuel consumption.